Applying quality tools to reduce Other Waste in a disposable diaper factory - Santos, Maylane Neres Costa; Silva, Natália Macêdo e; Santos, André de Mendonça; Andrade, Eron Passos; Damm, Djoille Denner (Brazilian Journal of Production Engineering, 2025)
This study aimed to identify and mitigate waste in the manufacturing of disposable diapers in a factory in Bahia, using quality tools. The company, which is the object of study, deals with complex industrial processes, which include the combination of raw materials such as cellulose, superabsorbent polymers and non-woven fabrics for the production of non-durable consumer goods, with an emphasis on personal hygiene. The production system is automated, on a large scale, but requires strict control to prevent waste. Using tools such as brainstorming, Pareto chart, Ishikawa diagram and the 5 Whys, this study focused on identifying and mitigating the causes of waste of primary materials, called Other Waste. The application of the tools had the participation of the operations team and validation took place in daily meetings, which culminated in training actions, operational adjustments and predictive maintenance. The results demonstrated an average reduction of 51.6% of waste from machine 1 and 65.9% from machine 2, evidencing the effectiveness of the implemented actions. In addition to improving economic efficiency, this research highlighted the importance of integration between operational and maintenance teams, promoting a cultural change that strengthens trust in automated systems.